Analisis Kendala Pembelajaran IPS terhadap Isu Global yang Dipengaruhi Kemajuan Teknologi - Dzikra Tsabita Azalea; Munawaroh, Aisyatun; Setiyoko, Didik Tri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze various obstacles in Social Sciences (IPS) learning related to global issues that are increasingly influenced by technological advances, through literature study methods. Social studies has a strategic role in shaping students' understanding of social, economic, cultural, and political aspects, as well as fostering global awareness in the digital era. However, the effectiveness of social studies learning still faces a number of obstacles, especially low student interest because the material is considered boring, too theoretical, and less interesting than digital entertainment. In addition, less interactive learning methods, limited facilities, unconducive classroom environment, and lack of parental support also worsen the quality of learning. Through a comprehensive literature review, this study identifies several relevant learning strategies to overcome these constraints, including ProjectBased Learning, technology integration, and contextual approaches. These three strategies allow students to learn actively, critically, and collaboratively by relating social studies materials to global issues and real phenomena. This research provides theoretical contributions to the development of social studies learning models that are adaptive to technological developments, as well as practical benefits for teachers, schools, and policymakers in creating social studies learning that is more interesting, meaningful, and relevant to the global challenges of the 21st century.